Multivariate geostatistical modeling of seismic data: Case study of the Late Pleistocene paleodelta architecture (SW off-shore Hainan Island, south China sea). (February 2022) - Miluch, Jakub; Maciąg, Łukasz; Osadczuk, Andrzej; Harff, Jan; Jiang, Tao; Chen, Hongjun; Borówka, Ryszard Krzysztof; McCartney, Kevin
Abstract: This study investigates a Late Pleistocene paleodelta located on the northwestern shelf of South China Sea, in Beibu Gulf southwest offshore Hainan Island, and details data acquisition to generate reliable 3D geometric models. High-resolution seismic profiles and geostatistical interpolation tools, combined with assumptions about paleo-sea-level changes, allow examination of paleodelta geometrical features. This paper presents methods and procedures that generate morphological models of seismic reflector surfaces and sediment thicknesses. Reliable model-based maps require several trials to optimize various kriging parameters, in particular semivariogram interpretation. Two semivariogram models, the widely-used spherical and nested Gaussian-power methods, are described and applied. Uncertainty among directionally undersampled seismic data is here improved by reduced kriging variance and validation by "goodness-of-fit". As the investigated paleodelta extends beyond the profile area, an innovative method for data extrapolation is applied based on paleogeographic and paleoeustatic data. Obtained results allow estimation of paleodelta volume and mass and riverine annual sediment discharge to reconstruct Gulf paleogeographic evolution and pathways of sediment distribution. Highlights: "Hainan Delta" was reconstructed using geostatistical modeling of seismic data. Ordinary kriging and nested models were used to enhance maps' reliability. Innovative extrapolation method allowed to extend the model to undersampled areas.